Borderless Flows in Federspiel’s Die Ballade Von Der Typhoid Mary - Charlotte Melin (Studies in 20th & 21st Century Literature, 2020)
Jürg Federspiel’s novel Die Ballade von der Typhoid Mary (1982) offers a fictionalized account of the notorious heroine’s life that ultimately sympathizes with her plight as an immigrant who faced exclusionary cultural barriers. Drawing on Rob Nixon’s concept of “slow violence” and recent approaches developed by material ecocriticism theory, my essay reinterprets this work from an environmental humanities perspective. The interpretation focuses on the interconnection of discourses related to disease, food, and pollution flows. Exploration of these themes leads to the conclusion that Federspiel’s work was prescient in its parallel engagement with both immigration issues and the emerging environmental concerns of its time. Since global migration today is increasingly understood to have climate change as its proximate cause, the novel deserves renewed attention for the insights it offers into the intersection of environment, transnational mobility, and class divides. Beyond illustrating the social tensions present in America during the Gilded Age and in the 1980s, it presents perspectives on historical conditions that remain relevant to debates about migration today.
Keywords: Material ecocriticism; slow violence; environment; pollution; disease; postmodernism